THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON TEACHER PERFORMANCE IN SENIOR HIGH SCHOOLS IN TANGERANG REGENCY - Sri Rahmayanti; Ruknan Ruknan; Yulita Pujilestari; Lili Nurlaili (Jurnal Manajemen Pendidikan, 2026)
Teacher performance is a critical factor in determining the quality of education at the senior high school level. Enhancing teacher performance requires effective leadership practices, a strong organizational culture, and high levels of work motivation. This study aims to examine the influence of transformational leadership style, organizational culture, and work motivation on teacher performance in senior high schools located in Tangerang Regency. A quantitative research approach was employed using a survey method. The population of the study consisted of teachers from public and private senior high schools in the region, and a total of 119 teachers were selected as respondents through proportional random sampling. Data were collected using structured questionnaires that were tested for validity and reliability to ensure measurement accuracy. The collected data were analyzed using descriptive statistics and inferential statistical techniques, including classical assumption tests, multiple linear regression analysis, partial significance tests (t-tests), simultaneous significance tests (F-tests), and coefficient of determination analysis (R²), with the assistance of SPSS software. The results of the study demonstrate that transformational leadership style has a positive and statistically significant effect on teacher performance.